Taxonomic study of Black-flies (Diptera: Simuliidae) larvae in Al Arab River (Lattakia, Syria) - Rajab, Eva; Zeini, Adib; Fadel, Ekbal (International Journal of Scientific Research in Biological Sciences, 2020)
Black-flies larvae samples were collected monthly from one fixed site in AL Arab river (Lattakia, Syria) for a year during the period from December 2017 till October 2018. Slides were prepared and morphological characteristics of last-instar larvae (matured) and pupae were used to determine the classification of species. As a result, eleven species (Metacnephia persica; Prosimulium tomosvaryi; Simulium. (Eusimulium) angustipes; S. (welhelmia) pseudoequinum; S. (simulium) kiritshenkoi; S. (Obuchovia) auricuma; S. (Simulium) trifasciatum; S.( Nevermannia) ruficorne; S. (Eusimulium) aureum; S. (Eusimulium) . sp and S. (welhelmia) paraequinum) belonging to three genera (Metacnephia , Prosimulium and Simulium) were reported, ten species of them were reported for the first time in Syria. This is the first study of black-flies larvae taxonomy in Syria.